Determinants of language change in the Gurage area of Ethiopia - Feleke Tekabe Legesse (Journal of World Languages, 2023)
This study aims to examine linguistic and non-linguistic determinants that contribute to language change in the Gurage area of Ethiopia. The linguistic and non-linguistic determinants were investigated by combining methods of dialectometry and mutual intelligibility. Principally, the study was interested in the potential influences of three linguistic factors (mutual intelligibility, contact-induced diffusion of linguistic features, and borrowing from dominant languages) and four non-linguistic factors (between-speakers contact, geographical distance, population size, and attitude of the speakers). Statistical analyses performed on the aforementioned factors show that the linguistic determinants significantly contribute to language change in the Gurage area. Geographical distance, attitude of the speakers, and contact among the speakers are the major non-linguistic contributors. Population size has a marginal influence.